Application of a computer sound card for measurement of mechanical vibrations - Barros,Everaldo de (2015)
This paper presents a data acquisition and analysis system based on a computer sound card for measuring and processing random vibration signals. This system turns the computer into a two-channel measurement instrument which provides sample rate, simultaneous sampling, frequency range, filters and others essential capabilities required to perform random vibrations measurements. An easy-to-use software was developed for vibration monitoring and analysis, including facilities for data recording, digital signal processing and real time spectrum analyzer. Since the tasks of vibration data acquisition frequently require expensive hardware and software, this versatile system provides students a very accurate and inexpensive solution for experimental studying mechanical vibrations.